TEACHING CRITICAL THINKING SKILLS (KONFERENSIYA, 2025)
Critical Thinking (CT) has been increasingly recognized as a vital skill forstudents, serving as a key indicator of the quality of their learning. To cultivate effectivecritical thinkers, it is essential to integrate CT into the curriculum and teaching methodsacross all grade levels. This research presents a systematic review of existing literatureon the instruction of CT skills, culminating in a conceptual framework that outlines fourprimary debates among researchers in the field. One significant debate centers onwhether technology can enhance students' CT skills. The findings from current practicessuggest that teaching methods often prioritize subject matter over the development ofCT. This indicates a notable gap in the instruction of CT skills, particularly regardinginnovative teaching strategies and the incorporation of new technologies. Furthermore,the research underscores the necessity for additional studies aimed at exploring novelapproaches to teaching CT skills effectively. In summary, while there is a growingrecognition of the importance of CT in education, there remains a critical need for moreinnovative and technology-driven methods to effectively teach these skills in theclassroom